Theoretical analysis of strategies for improving p‐type conductivity in wurtzite III‐nitride devices for high‐power opto‐ and microelectronic applications. Issue 3 (27th February 2014) - Satter, Md. Mahbub; Liu, Yuh‐Shiuan; Kao, Tsung‐Ting; Lochner, Zachary; Li, Xiaohang; Ryou, Jae‐Hyun; Shen, Shyh‐Chiang; Detchprohm, Theeradetch; Dupuis, Russell D.; Yoder, P. Douglas
Abstract: Achieving high p‐type conductivity is one of the most significant bottlenecks to the efficient operation of wurtzite III‐N based optoelectronic and microelectronic devices. Through judicious volumetric redistribution of fixed negative polarization charge, compositionally graded layers may be exploited to achieve nearly flat valence band profiles free from electrostatic barriers to hole injection into the active region. This may potentially ameliorate problems associated with poor p‐type conductivity and inefficient hole transport that complicates the design of DUV laser diodes and light emitting diodes. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)